An exploration of co-development within the Malaysian automotive industry - Bin Yahaya, Nordin (Cranfield University, 2010)
This is a study of Malaysian vehicle manufacturer-supplier relationships in the product development process. The collaboration, referred to as co- development, is highly important in order for vehicle manufacturers to remain competitive within this area of globalisation. So far, there have been no studies on the above subject area within Malaysia, which therefore makes this study both valuable and immensely important. The motivation comes from the uniqueness of the Malaysian automotive industry, which is newly established compared to other countries, and which has also been protected by the Government since the establishment of first National Car company in the 1980s. The study has adopted a qualitative approach through exploratory study, and aims to explore in-depth the co-development practices within Malaysia. With the adoption of a case study research strategy, data is collected by means of interviews with consideration to both sides, i.e., local vehicle manufacturers and their suppliers. It was found that, within Malaysia, two different approaches of co-development exist. First, the local suppliers mostly have low design capabilities, and the local vehicle manufacturer-supplier relationship exists only in terms of manufacturing components. Moreover, local suppliers have not become involved in the design process, but have received detailed drawings from vehicle manufacturers. However, they nevertheless have a freedom to manufacture the product without significant interference from the vehicle manufacturer. In this study, this type of supplier is labelled as a ‗freedom to manufacture‘supplier. In contrast, ‗freedom to design, develop and manufacture‘suppliers—which are mostly overseas suppliers—are involved in the design process at a very early stage. They are invited to participate at this point of the product development process in order to cater to the vehicle manufacturer‘s limited knowledge regarding the product. The study provides insight into what has happened with regards to the Malaysian vehicle manufacturer-supplier relationship in the product development process. It gives an indication of and new knowledge regarding the co-development of the newly established automotive industry in Malaysia.